НРАВСТВЕННАЯ КУЛЬТУРА ЛИЧНОСТИ И ЕЕ РОЛЬ В ОБЩЕСТВЕННОЙ ЖИЗНИ ЧЕЛОВЕЧЕСТВА - Умарова Насиба Эркиновна, Усманова Манзура Исаковна (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2024)
This article discusses the structure and analysis of the elements of human moral culture. Moral culture arises within the framework of a specific ethical and cultural tradition. In the system of a particular moral culture, moral ideals, value orientations, moral feelings, and moral beliefs are formed.